Strip-searching as abjectification: Racism and sexual violence in British policing - Duff, Koshka (Theoretical criminology, 2025)
This article examines police strip-searching practices in the UK. Drawing on newly acquired Freedom of Information data, publicly available testimonies, thematic analysis of official literature and media reports, and first-hand experience, we advance three arguments. First, strip-searching is used systematically, not exceptionally, and targets young people and people of colour, especially Black young men and boys. Second, strip-searching in practice is demonstrably excessive when measured against its stated rationales of ‘crime’ detection and ‘caring’ for detainees; we unpick the circular logics through which it is legitimized in official and public discourse. Third, drawing on Sharpe's notion of the abject, we argue that strip-searching, as a form of normalized sexual violence folded into the rubric of ‘care’, is part of a project of abjectification that aims to exclude the individuals and groups it targets from social and political subjecthood.